Linking Digital Literacy to Workforce Development and Macroeconomic Growth - Nurul Fadilah Aswar (PT. Maju Malaqbi Makkarana, 2026)
This study examines the linkage between digital literacy, workforce development, and macroeconomic growth in the context of an increasingly digitalized economy. Moving beyond descriptive approaches, it investigates how digital competencies function as a critical mechanism shaping labor productivity, innovation capacity, and economic performance. Using cross-sectoral data and workforce survey evidence, the study analyzes the extent to which digital skills contribute to workforce adaptability and organizational efficiency. The findings reveal that higher levels of digital literacy significantly enhance workforce development by improving skill alignment, fostering innovation, and increasing competitiveness across industries. At the macro level, these improvements translate into measurable contributions to economic growth through productivity gains and structural transformation. Furthermore, the study underscores the importance of multi-stakeholder collaboration among educational institutions, industry, and government in designing integrated digital literacy programs. Such coordinated efforts are essential to ensure sustainable skill development and long-term economic resilience. This research contributes to the literature by providing an integrated perspective that explicitly links digital literacy to both workforce development and macroeconomic outcomes, offering practical implications for policymakers and stakeholders in shaping inclusive and sustainable growth strategies.